Pelanggaran Ham Dalam Tragedi Kanjuruhan 2022: Perspektif Keadilan dan Perlindungan Hak Asasi Manusia - Agustin, Elinda Azis Tri; Mumtaz, Khansa Khairunnisa; Mapandiy, Vivian Daniella; Zulfariza, Alya Annisa; Pakpahan, Firly Natasha; Rahman, Naziva Azzahra; Putri, Audrey Rasya Novianto; M, Mulyadi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Human rights (HAM) guarantee protection and justice for every individual, including in organizing sporting events. Although regulated in national and international regulations, human rights violations still often occur, especially in excessive crowd control. The Kanjuruhan tragedy on October 1, 2022 is clear evidence of this negligence. The incident caused 135 fatalities and hundreds more were injured due to mass panic triggered by the use of tear gas in the stadium. This incident highlighted the weakness of the security system and the lack of protection for supporters. The actions of the authorities in the Kanjuruhan tragedy were considered excessive and violated FIFA regulations, especially the use of tear gas which actually worsened the situation. In response, the government formed an Independent Joint Fact-Finding Team (TGIPF) to investigate this incident and take action against those responsible. However, many consider that the verdict against the defendant does not reflect justice for the victims and their families. This tragedy is a bitter reminder of the weakness of security in stadiums, encouraging reform and improvement of regulations for the safety of spectators. This study emphasizes the importance of a more humane security policy, where security is not only effective but also respects human rights. Comprehensive reform and strong commitment to human rights protection are important steps to prevent similar incidents from happening again in the future.